Self Efficacy In Career Decision Making - Kurniawati, Erni; Mulawarman; Mulyani, Petra Kristi; Wasono, Andy; Arinata, Firdian Setiya; Mubarak, Muh Azhar (Coution: Journal Counseling and Education, 2025)
This study aims to analyze the impact of self-efficacy on career decision-making among vocational high school (SMK) students and identify the factors that influence it. The method used is a Systematic Literature Review (SLR) with the PRISMA approach, which includes the identification, screening, evaluation, and interpretation of articles from the Taylor & Francis and Sage Journal databases. Of the 5,533 articles found, four relevant articles were analyzed. The results show that self-efficacy plays a significant role in building students' confidence in choosing a career that suits their interests and potential. Factors such as social support, academic experience, family environment, work experience, and active decision-making strategies contribute significantly to increasing self-efficacy. In addition, interventions such as career guidance, self-exploration training, job simulations, and career workshops have proven effective in helping vocational high school students face the challenges of an increasingly complex working world. This study concludes that strong self-efficacy can help vocational high school students achieve optimal career readiness. It is necessary to develop innovative and integrated career guidance programs, involving schools, parents, and industry, to support students in making informed career decisions. This study provides valuable insights for guidance and counseling teachers in improving more effective career guidance services.